2010
DOI: 10.1186/1752-1947-4-110
|View full text |Cite
|
Sign up to set email alerts
|

Papillary thyroid cancer associated with syndrome of inappropriate antidiuresis: a case report

Abstract: IntroductionThe syndrome of inappropriate antidiuresis is the most common cause of euvolemic hypo-osmolality. This syndrome is associated with a wide variety of diseases. However, its most frequent causes are related to malignancies, especially lung cancer. In this case report, we describe an unknown association of the syndrome of inappropriate antidiuresis with papillary thyroid cancer.Case presentationWe present the case of a 71-year-old Caucasian, German woman with marked hyponatremia and neurological sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 17 publications
(17 reference statements)
0
3
0
4
Order By: Relevance
“…Atrophoderma 1 27 Polymyositis 1 28 Dermatomyositis 8 [29][30][31][32][33] Perforating collagenosis 1 34 Myelopathy 1 35 Ectopic hCG secretion 2 24, this case Ectopic parathyroid hormone secretion 1 36 Panuveitis 1 37 Syndrome of inappropriate antidiuresis 1 38 Cerebellar syndrome and sensory ganglionopathy 1 39 Epidermolysis Bullosa Acquisita 1 40 Propriospinal myoclonus 1 41 Systemic lupus erythematosus 1 42 Polymyalgia rheumatica 1 43 Retinopathy 1 44 Neutrophilia & eosinophilia due to granulocyte-macrophage colony-stimulating factor 1 45 FTC Leukocytosis 1 46 Hypertrophic osteoarthropathy 1 47 ATC Ectopic hCG secretion 5 5 Hypertrophic osteoarthropathy 1 48…”
mentioning
confidence: 99%
“…Atrophoderma 1 27 Polymyositis 1 28 Dermatomyositis 8 [29][30][31][32][33] Perforating collagenosis 1 34 Myelopathy 1 35 Ectopic hCG secretion 2 24, this case Ectopic parathyroid hormone secretion 1 36 Panuveitis 1 37 Syndrome of inappropriate antidiuresis 1 38 Cerebellar syndrome and sensory ganglionopathy 1 39 Epidermolysis Bullosa Acquisita 1 40 Propriospinal myoclonus 1 41 Systemic lupus erythematosus 1 42 Polymyalgia rheumatica 1 43 Retinopathy 1 44 Neutrophilia & eosinophilia due to granulocyte-macrophage colony-stimulating factor 1 45 FTC Leukocytosis 1 46 Hypertrophic osteoarthropathy 1 47 ATC Ectopic hCG secretion 5 5 Hypertrophic osteoarthropathy 1 48…”
mentioning
confidence: 99%
“…Die paraneoplastische Genese eines SIADH ist in der Literatur gut beschrieben und kommt vor allem bei Kopf-Hals-Tumoren und beim kleinzelligen Bronchialkarzinom vor, ist aber grundsätzlich bei sehr vielen Tumorentitäten beschrieben, so auch bei Lymphomen [11,12]. In diesem Fall zeigte sich laborchemisch eine Hyponatriämie infolge eines paraneoplastisch bedingten SIADH sowie eine Paraneoplasie der Haut in Form eines schweren, generalisierten, papulo-pustulösen Exanthems mit massivem, therapie-resistentem Pruritus.…”
Section: Konsequenz Für Klinik Und Praxisunclassified
“…In a study of 28 patients with Hurthle cell neoplasms of which 19 were malignant, and having distant metastasis during presentation, no paraneoplastic manifestations were described [9]. A case report by Bier et al reported a 71 year old woman with papillary carcinoma of thyroid presenting with SIADH [10]. Kalliabakos reported 31 year old patient who presented with polymyositis along with papillary carcinoma of thyroid [11].…”
Section: Discussionmentioning
confidence: 99%